K‐t GRAPPA accelerated four‐dimensional flow MRI in the aorta: Effect on scan time, image quality, and quantification of flow and wall shear stress. Issue 2 (4th September 2013) - Schnell, Susanne; Markl, Michael; Entezari, Pegah; Mahadewia, Riti J.; Semaan, Edouard; Stankovic, Zoran; Collins, Jeremy; Carr, James; Jung, Bernd
<x xml:space="preserve">Abstract</x> Purpose The purpose of this study was to evaluate the utility of k‐t parallel imaging for accelerating aortic four‐dimensional (4D)‐flow MRI. The aim was to systematically investigate the impact of different acceleration factors and number of coil elements on acquisition time, image quality and quantification of hemodynamic parameters. Methods k‐t accelerated 4D‐flow MRI (spatial/temporal resolution = 2.1 × 2.5 × 2.5 mm/40.0 ms) was acquired in 10 healthy volunteers with acceleration factors R = 3, 5, and 8 using 12‐ and 32‐channel receiver coils. Results were compared with conventional parallel imaging (GRAPPA [generalized autocalibrating partial parallel acquisition], R = 2). Data analysis included radiological grading of three‐dimensional blood flow visualization quality as well as quantification of blood flow, velocities and wall shear stress (WSS). Results k‐t GRAPPA significantly reduced scan time by 28%, 54%, and 68%, for R = 3, 5, and 8, respectively, while maintaining image quality as demonstrated by overall similar image quality grading. Significant differences in peak WSS (diff12ch = −5.9%, diff32ch = 18.5%) and mean WSS (diff32ch = 13.9%) were found at the descending aorta for both receiver coils for R = 5 (PWSS < 0.04). Peak velocity differed for R=8 at the aortic root (−7.4%) and descending aorta (−12%) with PpeakVelo < 0.03. Conclusion k‐t GRAPPA acceleration with a 12‐ or 32‐channel receiver coil and an acceleration of 3 or 5 can compete with a standard GRAPPA R = 2 acceleration. Magn Reson Med 72:522–533, 2014. © 2013 Wiley Periodicals, Inc.